Sociodemographic And Social Activities Factors Associated With Premarital Sex Behaviour Among Late Adolescents In Semarang - Febrianti, Putri; Udijono, Ari; Saraswati, Lintang Dian (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2021)
Introduction: Premarital sexual behavior is one of the complex problems faced by adolescents. This behavior is increasingly prevalent throughout the world, especially in Indonesia. This study aims to determine the sociodemographic factors (gender, and monthly allowance) and social activities related to premarital sexual behavior in late adolescence in Semarang City.Methods : This research is a quantitative study with a cross sectional approach. The number of samples was 400 respondents aged 18-22 years using consecutive sampling technique. This study used univariate and bivariate analysis using the chi-square test.Results: The results showed that gender (p = 0,000), monthly allowance (p = 0,000) and social activity (p = 0,000) had a relationship with premarital sexual behavior in late adolescence.Conclusion: It is necessary to establish youth programs at SMA / SMK / equivalent and university levels to develop self-confidence and life skills with an increasing the ability of adolescents to avoid and / or reduce risky sexual behavior.